2022
DOI: 10.1007/s43630-022-00305-0
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical defense as trait of fungi from Cortinarius subgenus Dermocybe

Abstract: The photobiological activity of ten colorful species belonging to subgenus Dermocybe of the basidiomycete genus Cortinarius was investigated. Extracts of all species produced singlet oxygen and are thus photoactive. Pigment analysis was performed and showed similarities of the anthraquinone pigments across the species in dependency to their respective pigmentation types. Detailed content analysis of the pigments in the whole agaricoid fruiting body compared to the three different tissue types (pileus, stipe, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…A pigment database is also a prerequisite allowing to identify taxa based on pigment profiles. Modern chemical analysis methods as applied in this work, have now shown, that pigment profiles of dermocyboid Cortinarius species are indeed useful and valid characters for species delimitation, especially when pigment concentrations are considered in addition to pigment composition (Hannecker et al 2023 ). Pigments or fingerprints of other metabolites, e.g., of volatile organic carbons, have also proven to be suitable tools for species recognition in fungi (Peintner et al 2019 ; Telagathoti et al 2021 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A pigment database is also a prerequisite allowing to identify taxa based on pigment profiles. Modern chemical analysis methods as applied in this work, have now shown, that pigment profiles of dermocyboid Cortinarius species are indeed useful and valid characters for species delimitation, especially when pigment concentrations are considered in addition to pigment composition (Hannecker et al 2023 ). Pigments or fingerprints of other metabolites, e.g., of volatile organic carbons, have also proven to be suitable tools for species recognition in fungi (Peintner et al 2019 ; Telagathoti et al 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…The list of the collections of species examined in this study are provided (See Additional Material Table 2 ). The material was collected in samples of around 5 to 10 specimens, apart from a few smaller samples, and includes species of the subgenus Dermocybe used in our earlier studies (Siewert et al 2022 ; Hannecker et al 2023 ). Material was collected in Central Europe, mostly in coniferous alpine habitat.…”
Section: Methodsmentioning
confidence: 99%
“…Many basidiomycete pigments show structural similarity with plant pigments, which are known for light-activated defense strategies such as the production of radical oxygen species (Siewert, 2021). A first case study showed that some pigments of species of Cortinarius subgenus Dermocybe are photoactivated and had toxic effects on a glassworm species (Hannecker et al, 2023).…”
Section: Biotic Factorsmentioning
confidence: 99%